Book production in the Caribbean : a concise guide for authors, publishers and printers - Henry, Maureen (The author St. AugustineTT, 1994)
Seeks to provide guidelines for publishers and printers so that they would be able to produce books of an acceptable bibliographic quality. Discusses aspects of the International Standard Serial and Book Number, copyright and legal deposit.